Cooperation and Empire Local Realities of Global Processes - Bührer, Tanja 1974-; Eichmann, Flavio; Förster, Stig 1951-; Stuchtey, Benedikt 1965- (Berghahn Books, 2017)
While the study of "indigenous intermediaries" is today the focus of some of the most interesting research in the historiography of colonialism, its roots extend back to at least the 1970s. The contributions to this volume revisit Ronald E. Robinson's theory of collaboration in a range of historical contexts by melding it with theoretical perspectives derived from postcolonial studies and transnational history. In case studies ranging globally over the course of four centuries, these essays offer nuanced explorations of the varied, complex interactions between imperial and local actors, with particular attention to those shifting and ambivalent roles that transcend simple binaries of colonizer and colonized